The role of ubiquinone supplementation on osteogenesis of nonvascularized autogenous bone graft - Irham Taufiqurrahman; Achmad Harijadi; Roberto M. Simanjuntak; Coen Pramono D; Istiati Istiati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Ubiquinone is one of food supplement which is known have positive effect in wound healing. However the study to evaluate the possible role of ubiquinone in bone healing in autogenous bone grafting after mandibular resection has not been studied. An in vitro study is required to evaluate whether ubiquinone or coenzyme Q-10 (CoQ10) has a positive effect on osteogenesis. Viability test of CoQ10 and a model of osteogenic-induced and hypoxic-condition mesenchymal stem cell culture were established to support the study. Purpose: The study was made to evaluate the role of ubiquinone in osteogenesis by analyzing the toxicity effect and the optimal dose of CoQ10 that might interfere in bone marrow derived mesenchymal stem cell (BM-MSC) that was dose in cell culture medium. The BM-MSC culture under hypoxia condition were also observed. Method: The toxicity and the optimum viability concentration of ubiquinone were observed using MTT assay. The osteogenic differentiation under hypoxic condition was done on BM-MSC in osteogenic medium that composed of ascorbic acid, glycerolphosphate and dexamethasone in hypoxia chamber for 21 days. Osteogenic differentiation and cellular hypoxia features were tested with immunocytochemical staining using anti-Runx2 and anti-HIF1α monoclonal antibody, respectively. Result: The maximum density value of 1.826 was found in the group of ubiquinone concentration of 75μM/ml, increasing of in concentration of ubiquinone resulted with the decrease ofoptical density of CoQ10. Statistic analysis using Anova showed with no significant difference among groups with various concentration. Immunocytochemical staining showed that Runx2 expression in 3% hypoxia group (p<0.05). Conclusion:Ubiquinone was found non toxic in its optimum dose of 75μM/ml, showed by optimum result in the expression ofRunx2 and HIF1α further study is necessary to evaluate the angiogenic and osteogenic effect ofubiquione.